Factors Related to the Event Hypertension in Farmers - Solehah, Eka Lutfiatus; Saputra, I Kadek Dwi Arta; Ariantini, Nyoman Sri (CV. Global Health Science Group, 2024)
Pesticides are materials that are widely used in various sectors, improper and correct use of pesticides can cause health problems where pesticides can cause hypertension because pesticides that enter the human body will be able to increase the enzyme acetylcholinesterase or Ache, so that there will be an accumulation reaction in the joints. Clinogenic neuro-effectors and autonomic ganglion which have an impact on the emergence of hypertension problems. The method in this research uses a quantitative research design with a cross-sectional analytical approach, the sampling technique in this research uses a total sampling technique from all workers totaling 17 respondents who work as farmers, the data collected is primary data and a univariate analysis test is carried out and bivariate analysis with Chi-square test to find relationships. The results of this research found that 64.7% of respondents experienced hypertension and 35.3% did not experience hypertension. Based on the data analysis carried out, it was found that the incidence of hypertension was significantly higher in the age group ≥ 30, working period ≥ 8years, longwork ≥ 8O'clock,smoking status is yes and PPE equipment is not good with a p value <0.05.